The History of Global Climate Governance - Gupta, Joyeeta (Cambridge : Cambridge University Press, 2014)
What has happened globally on the climate change issue? How have countries' positions differed over time, and why? How are problems and politics developing on an increasingly globalised planet, and can we find a solution? This book explores these questions and more, explaining the key underlying issues of the conflicts between international blocs. The negotiation history is systematically presented in five phases, demonstrating the evolution of decision-making. The book discusses the coalitions, actors and potential role of the judiciary, as well as human rights issues in addressing the climate change problem. It argues for a methodical solution through global law and constitutionalism, which could provide the quantum jump needed in addressing the problem of climate governance. This fascinating and accessible account will be a key resource for policymakers and NGOs, and also for researchers and graduate students in climate policy, geopolitics, climate change, environmental policy and law, and international relations.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).